Decreased Absolute Number of Circulating Regulatory T Cells in Patients With Takayasu’s Arteritis - Jia, Wen; Fu, Zi-Li; Wang, Xia; Luo, Jing; Yan, Cheng-Lan; Cao, Jian-Ping; Yan-Liu,; Xie, Jian-Fang; Liu, Guang-Ying; Gao, Chong; Li, Xiao-Feng (Frontiers in Immunology, 2021)
Background: Takayasu arteritis (TA) is a type of primary large vessel vasculitis . Th1, Th17, and Tfh cells have been reported to be associated with TA relapse.. However, relationship between regulatory T cells (Tregs) and TA remains unclear. Objective: To analyze the levels of circulating lymphocytes, especially Treg cells (CD4+CD25+FOXP3+T cells ) and serum cytokines in TA patients and explore their relationship with their changes and TA disease activity. Methods: A total of 57 TA patients and 43 sex- and age-matched healthy controls (HCs) were enrolled. According to NIH standards, 36 patients were had active disease status. Flow cytometry combined with counting was used to detect the absolute numbers and ratios of Th1, Th2, Th17 and Treg cells in the peripheral blood of all subjects. Magnetic bead-based multiplex immunoassay was used to detect cytokines. Results: Compared to HCs, the absolute number and proportion of peripheral Treg cells in TA patients was significantly decreased, while Th17 cells were significantly increased. Furthermore, compared to the inactive group, the TA active group had significantly increased levels of interleukin(IL)-6, IL-10, and tumor necrosis factor (TNF)-α, but lower IL-10 levels. The absolute number of Th2 cells was negatively associated with platelet (PLT) and NIS scores in TA patients.The proportion of Th2 cells was negatively associated with the erythrocyte sedimentation rate in TA patients. After treatment,Treg cells were markedly increased. Conclusion: There was a Th17-Treg cell imbalance a significant reduction in Peripheral Treg cells and an increased in Th17 cells in TA patients compared to HCs. The levels of IL-6, IL-10, IL-17 and TNF-α appeared to be related to disease activity.